Vaginal Approaches to the Management of Postpartum Hemorrhage - Mark Manning; Tiffany Moore Simas; Lynn Riza; Susan Pasquale (Association of American Medical Colleges, 2010)
Abstract Introduction This resource is a comprehensive tutorial for nonpharmacologic vaginal management of postpartum hemorrhage. Management methods addressed include uterine exploration and evacuation including dilation and curettage, and uterine tamponade techniques including uterine packing and use of commercial products. This module was prepared for use in residencies with significant obstetrical training but is appropriate for use by any individual seeking detailed information on initial conservative management of postpartum hemorrhage. It can be used in conjunction with postpartum hemorrhage simulation, in support of didactic sessions, as a stand-alone discussion, or review of the subject matter. Methods All procedures are presented as an overview with attached step-by-step instructional guides and videos. The presentation contains a narrated web-based presentation with embedded videos. There is a transcription of all audio narration so that the resource is usable for the hearing impaired. Results Pre- and posttests associated with this resource demonstrated a clear improvement in mastery of material as a result of using this module. All trainees completing the module reported that the module increased their knowledge "moderately" or "to a great extent." Additionally, all trainees reported that they agreed or strongly agreed that they would recommend the module to another learner. Discussion This module can be used in conjunction with a postpartum hemorrhage simulation, in support of didactic sessions, and as a stand-alone discussion or review of the subject matter.